PENGARUH MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY TERHADAP HASIL BELAJAR INFORMATIKA SISWA SMP - Rutria Sarah Hasna Tsabita Afaf; Gres Dyah Kusuma Ningrum; Hikmatul Afifah Fikriati; Muhammad Aulia Utama; Miftah Fadhlurrohman; Muhammad Naufal Baharudin; Nanda Defi Aprilianto; Rizky Rahmad Andre Anang (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
This research aims to investigate the effects of implementing Augmented Reality (AR)-based instructional media on the academic performance of ninth-grade students in the subject of Informatics. A quantitative method was adopted, utilizing a one-group pretest-posttest experimental design. The study involved 29 students from class IX D at SMP Negeri 25 Malang. Data collection was conducted through pretest and posttest evaluations, followed by analysis using normality testing, the Paired Sample T-Test, and N-Gain Score computation. The findings revealed a significant improvement in student’s academic outcomes following the use of AR media, with a t-test significance value of 0.000 and an average N-Gain score of 0.4198, indicating a moderate level of effectiveness. These results suggest that AR-based learning tools can effectively support students’ comprehension of Informatics and offer a creative alternative for classroom instruction. The results of this research provide a significant contribution to the effectiveness of using AR-based instructional media in improving student learning outcomes, which can serve as a creative and innovative solution to support more meaningful, interactive, and student-centered Informatics learning.